Aurelius Hospital Nilai / Siti Norfasehah Zolkeflei - Zolkeflei, Siti Norfasehah (Faculty of Business and Management, 2023)
Exclusively at "Aurelius Hospital Nilai," an exciting 6-month industrial training programme will begin. Aurelius Hospital Nilai (AHN), originally NCI Cancer Hospital, was founded in 1999. This company is based in Nilai, Negeri Sembilan, and it specialises in cardiology, general surgery, and other medical specialties. In addition to offering exceptional service, AHN prioritises client comfort. This hospital also aims to fulfil the demands and happiness of patients by offering the highest quality service. The hospital has health medicine expertise, experience, and management via the utilisation of modem technologies and additionally apply knowledge through qualified medical professionals’ services. People who desire to be treated here can obtain medical care from the firm. This hospital is assured of achieving its goals because of internal knowledge and new innovations. Industrial training is also one of the requirements for a university to award a certificate or bachelor's degree to a student. Some students may be able to apply what they learned at the university while in training. Furthermore, it allows the students to discover new things that they have never encountered before in their lives. It will directly educate students to be independent, to have confidence, to be capable, and to be prepared for the real-life world of work. The industrial training is expected to create and develop more capable UiTM students in all industries, which will lead to a more developed nation.